Perception of wine with protection of origin using free association: case study Mexico - Carla Zulema Jauregui-García; Anastacio Espejel-García; Ariadna Isabel Barrera-Rodríguez; Arturo Hernández-Montes; Landy Hernández-Rodríguez (Applied Food Research, 2024)
Social representations can be explored as an approach in food science to understand the type of information consumers have about a product. The objective of this study was to identify the social representations given to wine with protection of origin and Mexican wine, by consumers from four regions of Mexico, and to explore its valorization elements. The verbalization of the two wines was independently examined by the free association of words, through an Internet survey carried out on a sample of Mexican wine consumers (n = 615). Wine with origin protection was mainly represented by quality attributes in the Western, Central, and South regions of Mexico, and Mexican wine was conceptualized mainly with the identity of origin; in this case both stimuli formed a general tendency towards utilitarian meanings. The conceptualization of Mexicans regarding the two wines was distributed in both tangible and intangible categories; The representations granted in each region vary depending on the relationship that the culture of that area has with wine.